'Ought implies Can' and the law. Issue 4 (19th May 2018) - Fox, Chris; Feis, Guglielmo
Abstract: In this paper, we investigate the 'ought implies can' (OIC) thesis, focusing on explanations and interpretations of OIC, with a view to clarifying its uses and relevance to legal philosophy. We first review various issues concerning the semantics and pragmatics of OIC; then we consider how OIC may be incorporated in Hartian and Kelsenian theories of the law. Along the way we also propose a taxonomy of OIC-related claims.